Analisis Kualitas Daging Bebek Dengan Menggunakan Uji pH, Daya Ikat Air dan Uji Eber di Pasar Tradisional Kabupaten Kediri - Wirjatmadja, Roeswandono; Setyonugroho, Aji; Restijono, Era Hari Mudji; Sari, Dian Ayu Kartika (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2021)
This study aims to determine how the pH, water holding capacity and the Eber test or rot test on duck meat which taken in several traditional markets in Kediri Regency. The samples were taken as many as 30 samples from 3 different markets. From each market taken as many as 10 different samples in each market. The type of research is quantitative and descriptive using qualitative laboratory examinations. The results showed that for the pH test and water holding capacity there was no significant difference from the three markets, but in the Eber test that was carried out there were several positive and some negative samples. This is due to several factors that refer to the process of slaughtering animals, the type of animal, and the lack of sterilization of slaughterhouses and the lack of understanding for the community, therefore it is important to improve the quality of products that are safe, healthy, whole, halal.